Toward a Process Framework of Business Model Innovation in the Global Context: Entrepreneurship-Enabled Dynamic Capability of Medium-Sized Multinational Enterprises - Yangfeng Cao (Copenhagen Business School (CBS), 2015)
This PhD dissertation focuses on business model innovation (BMI), which plays a central role in explaining firm performance and is viewed as a source of competitive advantage. A recent global survey of more than 4,000 senior executives by the Economist Intelligence Unit found that the majority (54%) favoured BMI over product or service innovation as a source of future competitive advantage. Hence, the research on BMI is a salient topic for strategic management and entrepreneurship studies because it is central to a firm`s dynamic capability for novel value creation and novel value capture on a sustainable basis. Prior studies have argued that a business model can be only effective if it is designed properly for a specific context. In this sense, the business models of multinational enterprises (MNEs) should differ from those of domestic firms. Specifically, owing to the large gaps or distances in the economic and institutional contexts between advanced and emerging economies, as two sides of the global divide, cross-divide entry by MNEs, either from an advanced economy into an emerging economy as a top-down venture or from an emerging economy to an advanced economy as a bottom-up venture, will depend heavily on the novel business model designed to match the host context on the other side of the global divide. This is particularly true in the case of entering the mid-end market as the mainstream in the host economy. In addition, owing to the internal contextual dimensions of corporate size and age, the key challenge to a top-down venture seems more acute for medium-sized MNEs (MMNEs) than both large and small MNEs (the latter is often referred to as ‗born-global` firms). This is because MMNEs tend to have more limited resources than large MNEs, but less flexibility than small MNEs. Given the salience of the cross-divide context to MNEs as well as the paucity of research on MMNEs, this PhD dissertation focuses on how BMI occurs in the special context of cross-divide entry with a top-down venture for a mid-end market by MMNEs.
hdl:10398/9241
Keywords: 650